Species and Cladystic of Butterflies (Lepidoptera) in Malonas Village, Dampelas District, Central Sulawesi - Devi Devi; Mohammad Jamhari; Manap Trianto; Yulia Windarsih; Rafiqa Rafiqa; Fatmah Dhafir (Biology, Medicine, & Natural Product Chemistry, 2026)
Butterflies are a group of insects belonging to the order Lepidoptera, commonly known as scale-winged insects. This study examines the kinship relationships of butterfly species (Lepidoptera) based on morphological and morphometric characters in Malonas Village, Dampelas District, Central Sulawesi, an area that has not been previously documented. The objectives of this study were to identify butterfly characters through morphological and morphometric analyses and to construct kinship patterns that reflect the level of phylogenetic similarity among butterfly species. The research was conducted using a descriptive exploratory method. Sampling was carried out across all areas of Malonas Village, including residential areas, rivers, forests, and plantations, using a roaming survey method with free collection techniques, resulting in 10 butterfly species with a total of 30 individuals. Morphological and morphometric analyses included measurements of wing dimensions and major body parts. Data were analyzed using Principal Component Analysis (PCA) and the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) to determine kinship patterns. The UPGMA analysis showed that all species had a relatively high level of similarity, with a similarity value of approximately 0.78, indicating close relationships among species. PCA results revealed that two principal components (PC1 and PC2) explained 67.0% of the total morphological variation, accounting for 45.3% and 21.7%, respectively. Loading plots indicated that morphometric characters related to wing size and proportions were the main contributors to the formation of the principal components. Biplot graphs demonstrated species grouping based on similarities in morphological and morphometric characters, as well as positive correlations among variables within the same quadrant. The results of this study confirm that wing morphometric characters play an important role in explaining morphological variation and phylogenetic relationships of butterflies in Malonas Village.